Ailelerin Tatil Karar Sürecine Gençlerin Etkileri: Ankara İli Örneği / The Effects of the Youngs on the Family Vacation Decision Process: Ankara Case Study - Köşk, Ülker; Gürbüz, Ahmet (Journal of History Culture and Art Research, 2017)
Abstract Individuals who are members of a social group exhibit behaviors that may be similar or identical to that of the social group. It can be said that the individuals in a familiy, like in a social group, also have the same or similar thoughts, habits and behaviors. Having similar thoughts, habits and behaviors is the result of the individuals in the group being affected by each other. The individuals in the family can be influenced by each other in the decision-making process as well as with the many areas. This influence is multilinear, and we must say that it is possible for each of the family members to be potentially affected individually by all the members of the family. This research examines how families are influenced by their children’s thoughts during vacation decision-making. The universe of the research is young people aged 15-24 who reside in Ankara. As in most areas, families can be influenced by their children’s thoughts and ideas during holiday decision-making. In this research, according to all these information, it researched in the city of Ankara to examine the effects decision-making process of the families of young people aged 15-24. A total of 1160 surveys were conducted in the research and 15 surveys were not included in the study for various reasons. The results of the questionnaires were analyzed using SPSS 22.0 program interpreting the data obtained from the remaining 1145 questionnaires. Öz Bir sosyal gruba mensup olan bireyler, sosyal grubun davranış biçimi ile benzer ya da aynı sayılabilecek davranışlar sergilerler. Sosyal bir grup olan ailedeki bireylerin de aynı düşüncelere, alışkanlıklara ve davranışlara sahip oldukları söylenebilir. Benzer düşünce, alışkanlık ve davranışlara sahip olmanın temelinde grup içindeki bireylerin birbirlerinden etkilenmelerinin yer aldığı söylenebilir. Ailedeki bireyler birçok alanda olduğu gibi karar verme sürecinde de birbirlerinden etkilenebilirler. Bu etkilenme çok yönlü bir etkilenme olup aile bireylerinden herbirinin potansiyel olarak ailenin tüm bireylerinden ayrı ayrı etkilenmesinin mümkün olduğunu söylememiz gerekir. Bu araştırma, tatil karar verme sürecinde ailelerin, çocuklarının düşüncelerinden ne şekilde etkilendiklerini incelemektedir. Çalışmanın evrenini, Ankara’da ikamet eden 15-24 yaş arası gençler oluşturmaktadır. Araştırmada toplam 1160 anket uygulanmış olup çeşitli nedenlerle 15 anket çalışmaya dâhil edilmemiştir. Geriye kalan 1145 anketten elde edilen verilerin yorumlanması için SPSS 22,0 veri analiz programı kullanılarak anket sonuçları analiz edilmiştir.